A Review Paper on Detection and Mitigation of DDoS Attacks - Rutvij Upadhyay,; Dr. Shivam Upadhyay, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Distributed Denial of Service (DDoS) attacks have emerged as one of the most significant threats to the availability and stability of online services, leading to widespread disruptions and economic losses. DDoS attacks overwhelm targeted systems, networks, or services with excessive traffic, rendering them unable to function properly. The detection and mitigation of DDoS attacks require a combination of proactive strategies, real-time monitoring, and advanced defence mechanisms. This paper provides an overview of current approaches to DDoS detection and mitigation, focusing on methods such as traffic analysis, anomaly detection, machine learning techniques, and rate-limiting solutions. Additionally, it explores the role of cloud-based and hybrid defence systems, which leverage distributed resources for scalable protection. The paper also examines the challenges in defending against evolving attack vectors, including those involving botnets and amplification techniques, and proposes future research directions to enhance the resilience of critical infrastructures against these threats.